GUARDIANS OF PUBLIC SAFETY: SECURITY RISKS, CRIME PREVENTION PRACTICES AND INSTITUTIONAL SUPPORT SYSTEMS IN COMMUNITY MALLS IN THE PHILIPPINES - Rivera Bryan F (EPRA International Journal of Multidisciplinary Research (IJMR), 2026)
This study explored the lived experiences of security personnel, mall administrators, and tenants regarding security risks, crime prevention practices, implementation challenges, and institutional support systems within selected community malls in Antipolo City and Rodriguez, Rizal. The study aimed to develop a framework for enhancing security governance in community mall environments. A qualitative descriptive phenomenological design was employed. Twenty two (22) participants were selected through purposive sampling. Data were gathered through semi-structured interviews and analyzed using Colaizzi’s Seven-Step Phenomenological Method.The findings revealed that community malls face recurring property-related crimes, safety hazards, operational challenges, and resource constraints. Crime prevention practices include surveillance, access control, patrol operations, communication mechanisms, and preparedness activities. Institutional support is strengthened through collaboration among security personnel, mall administrators, tenants, public safety agencies, and local government units. Based on the findings, the Community Mall Security Governance Enhancement Framework (CMSGEF) was developed to strengthen security governance through risk management, crime prevention, stakeholder collaboration, capability enhancement, and continuous improvement. The framework promotes safe, secure, and resilient community mall environments.